Enabling Environment for Early Childhood Development: A Narrative Study of Preschools in Nepal - Ramila Subedi; Milan Shrestha (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
At present, creating environment for Early Childhood Development (ECD) has been given a great emphasis in Nepal’s educational context. However, a number of challenges are often narrated by the school leaders and teachers in creating environment to facilitate development of the children. Hence, this paper aims at exploring what experiences the preschools have assembled in course of creating environment for ECD. The paper is based on narrative inquiry where a teacher and two school leaders from three different institutional preschools of Kathmandu Valley were selected purposively as research participants for in-depth interview. Then, this study explored that school leaders and teacher were having a tough time for creating environment expected to support ECD though they narrated their awareness about the discourse. These challenges were narrated to have been occurred basically because of infrastructural constraints and divergent attitude of parents regarding how their children had to be learning at school. Moreover, lack of competent human resource to induce atmosphere for development of children was also recounted. Hence, the study implies collaborative environment between school leaders, teachers and parents to be created by school leaders to encourage teachers to adopt instructional strategies for strengthening atmosphere of ECD.